The consistency effect between applicants’ personality traits and job characteristics on employment advertisement: Perceived P-E Fitness, Organizational Attractiveness, and intention to job acceptance - Yang, Byunghwa (Korean Journal of Industrial and Organizational Psychology, 2014)
This study aims to examine the effect of consistency between applicants’ personality traits and job characteristics on employment advertisement. There are few empirical evidences about the consistency of personality traits and job characteristics, particularly in the employment advertisement, even though literature has shown that person-job (P-J) fit and person-organization (P-O) fit are strongly related to organization attractiveness and job choice decisions. The data were collected from a experiment of undergraduate students at a large Korean University. Using a ratin-square design and a eye-movement system in order to control over the order effect of stimuli presentations, the eighty subjects were given a series of employment advertisement one month after they completed the personalty test of NEO FFI-3. The employment advertisement material includes job requirements which represent a specific traits along with applicants’ personality traits. The result shows that the personality-based consistency between individuals traits and job characteristics is fairly associated with perception of person-job fit and intention to job acceptance. However, Results indicate a weak relationship between personality-based consistency and organizational attractiveness on employment advertisement. This study provides unique contributes to the literature by exploring how personality-based consistency between individuals and jobs influences perceived person-environment (P-E) fit and job choice decisions. Theoretical implications to the personality and recruitment literature are discussed along with practical suggestions to manager that are responsible for human resource management.